Dynamic response of the micro-perforated crab beam used in MEMS vibratory gyroscope device - The, Vu Van (Vietnam Journal of Mechanics, 2024)
This paper presents a study on the dynamic response of the micro-beams with the crab shape and cut-out holes on the whole operating faces of the beam to create the micro-perforated beam by using FEM simulation software. The obtained results show that the size and shape form of the cut-out holes affect the mechanical responses of the beam on which the holes distribute. The equivalent stiffness of perforated micro-beams decreases significantly with the increasing size of the holes on the beam operating face. And thence the major frequencies of the MEMS vibratory gyroscope system that consist of these micro-beams also decrease. The results of the study are basic for being used for optimizing the structure in subsequent research.